Maternal serum alpha-fetoprotein screening programs and quality control for laboratories performing maternal serum and amniotic fluid alpha-fetoprotein assays: policy statement. American Society of Human Genetics. (1987)
Maternal serum alpha-fetoprotein (MSAFP) values are used primarily but not solely to predict the occurrence of open neural tube defects in the fetus; their use for prediction of Down's syndrome is a new initiative under investigation. The test is a good one, as far as such a test can be, but it is imperfect, because false-negative and false-positive results both occur. In other words, it is not an infallible test. To use the test as effectively as is currently possible requires a program capable of supplying baseline values in sufficient number and the follow-up procedures necessary for interpretation of positive tests. In other words, it is not simply an office test. Because there is no effective treatment to relax the burden of neural tube defects in the large majority of patients, prevention of disease involves termination of pregnancy at present. In other words, use of the test is value laden and controversial for some sectors of society. Despite its imperfections, the need for an elaborate societal structure to apply it, and its value-laden context the test is considered by many as a necessary procedure to maintain normal standards of practice. Indeed, the American College of Obstetricians and Gynecologists issued a statement advising its fellows to be aware of the availability of MSAFP testing and to discuss such testing with patients. It is natural that confusion about protocol and anxiety about practice and its consequences are prevalent in this context. The American Society of Human Genetics (ASHG) offers here a statement about issues that affect MSAFP testing and the attendant pitfalls.